2013
DOI: 10.7883/yoken.66.195
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Human Metapneumovirus Infection Prevailing in Hospital Wards Housing Patients with Severe Disabilities

Abstract: SUMMARY: Epidemics of infectious diseases often occur at long-term inpatient facilities for patients with severe motor and intellectual disabilities. However, the pathogens causing these infections remain unknown in approximately half of such epidemics. Two epidemics of respiratory tract infection occurred in 2 wards in the National Hospital Organization Ehime Hospital (prevalence 1, 34 infected out of 59 inpatients in the A ward in September 2011; prevalence 2, 8 infected out of 58 inpatients in the B ward in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…The present study results are similar to those of reported outbreaks of metapneumovirus infection (12).…”
supporting
confidence: 93%
“…The present study results are similar to those of reported outbreaks of metapneumovirus infection (12).…”
supporting
confidence: 93%
“…53 However, the most common causes of hospitalization are bronchiolitis and pneumonia. 54 The average duration of fever in hMPV-positive cases is about 10 days, with a peak during the course of the illness. 55 Young adults with hMPV re-infection show mild cold and flu-like symptoms, with fever in a small proportion of infected cases.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…HMPV can produce asymmetric, acute interstitial pneumonia and bronchitis in immunocompromised adults, as evidenced by parenchymal airspace consolidations and bronchial wall thickening in chest computed tomography (CT) scans (32). Fever of Ͼ38°C, lymphopenia with monocytosis, increased C-reactive protein levels, and chest radiographs indicative of bronchitis and pneumonia have been also described for adults infected with HMPV (33). In healthy adults, experimental infection with HMPV produces symptoms including headaches, nasal congestion, pharyngitis, cough, hoarseness, cervical lymphadenopathy, and recurrence of herpes labialis (34).…”
Section: Clinical Symptoms Associated With Hmpvmentioning
confidence: 99%